2012
DOI: 10.1097/ruq.0b013e318274de66
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound-Guided Radiofrequency Ablation of Renal Tumors

Abstract: Although only limited long-term studies evaluating thermal ablation of renal masses have been performed, it appears that thermal ablation has a comparable 5-year success rate to that of partial or total nephrectomy. This technique is often used in patients who are not good candidates for partial or total nephrectomy. Contrast-enhanced ultrasound (CEUS) has been recently approved by the Food and Drug Administration for characterization of focal liver lesions in adults and pediatric patients. CEUS can be used of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…9 However, open surgery is always associated with a high risk for the patient, suppression of a patient's immune system and a significant mortality rate. Minimally invasive techniques as an alternative to open surgery, which became available during the 1990's for localized tumor treatment, such as radiofrequency ablation, 10 cryoablation, 11 direct laser ablation, 12 or high-intensity focused ultrasound (HIFU), are methods which use a range of energies for direct in situ tumor destruction through energy absorption and killing by heating or evaporation. Besides direct conversion of mechanical energy into heat, biological material may be damaged by the effects of mechanical stress caused by shock waves.…”
Section: Treatments Of Cancermentioning
confidence: 99%
“…9 However, open surgery is always associated with a high risk for the patient, suppression of a patient's immune system and a significant mortality rate. Minimally invasive techniques as an alternative to open surgery, which became available during the 1990's for localized tumor treatment, such as radiofrequency ablation, 10 cryoablation, 11 direct laser ablation, 12 or high-intensity focused ultrasound (HIFU), are methods which use a range of energies for direct in situ tumor destruction through energy absorption and killing by heating or evaporation. Besides direct conversion of mechanical energy into heat, biological material may be damaged by the effects of mechanical stress caused by shock waves.…”
Section: Treatments Of Cancermentioning
confidence: 99%
“…18 Currently, the most frequently used clinical contrast agent is SonoVue, which has already been registered and listed as a pharmaceutical agent in China. 25,26 Contrast-enhanced sonography is generally used clinically to identify and diagnose liver tumors, but recently, its use in studies of kidney, pancreatic, splenic, prostate, breast, and thyroid diseases, as well as abdominal trauma and other conditions, has been gradually increasing. [25][26][27][28] Gynecologic applications and studies have mainly focused on solid tumors in the uterus and ovary, [28][29][30][31] and to our knowledge, an evaluation of the contrast-enhanced sonographic features of ovarian endometrial cysts had not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a standard B‐mode US‐guided procedure, CEUS‐guided ablation therapy of small renal lesions has also shown improved success rates . Compared to CT/MRI, CEUS has high sensitivity, specificity, and accuracy in the detection of postablation residual tumors before the removal of the ablation probe, as mentioned in liver ablation (Figure ) …”
Section: Genitourinary Interventionsmentioning
confidence: 99%